Analisis Tingkat Keterampilan Jarak Pendek 30 Meter Kelas V di SD Negeri 40 Kota Bengkulu - Yucardo (SJS: Silampari Journal Sport, 2021)
This study aims to determine the level of sprint skills in a short distance of 30 meters in grade V SD Negeri 40 of Bengkulu City. The method used in this research is quantitative descriptive research method. The population in this study were the fifth grade students of SD Negeri 40 of Bengkulu City. While the samples in the were 26 students consisting of 13 female students and 13 male students. Instruments used in this study in the form of a 30 meters sprint skills test from the theory of Faruq and Fenanlampir (2015). The results of this study found that the 30 meters sprint skills of grade V SD Negeri 40 in Bengkulu City were included in the category of secondary school which had the highest percentage of 46.15%.